O Programa Saúde do Adolescente – PROSAD e a lei 12.015/09: uma avaliação dos profissionais envolvidos - Araújo, Rita de Cássia (2017)
The present study aims to analyze the implementation of the law of rape of vulnerable and comprehensive health care of adolescents and young people, from the perspective of health professionals, in a reference maternity, verifying what law 12.015, of 07 August 2009 brought again, not only for society in general through behavioral change, before the legal diploma, instituted by it; but with the purpose of presenting a reflection about the vulnerability portrayed in article 217-a, caput of the Brazilian Penal Code, making a brief discussion about the relative and absolute presumption of the device, as well as pointing the directions that led such discussion to an understanding of the relativization, by some of the doctrinaires, of the vulnerability of the victim over 12 and under 14; the research focused on health professionals who deal with adolescents with the profile mentioned above in a public maternity hospital in Fortaleza. We work with the descriptive research, because we understand that in its various forms, it works on data or facts taken from reality and does not interfere with them. In order to enable this important collection operation, it was used as the main instrument, application of semi structured interviews, with questions directed to the object of study, which helped us to know the opinion of the respondents, their thoughts and feelings. The specific objectives of this study were: to verify the professionals' understanding of the Comprehensive Health Care Policy for adolescents and young people and the law of rape of the vulnerable; identify how the multiprofessional team understands the penal device that deals with rape of vulnerable; verify possible conflicts faced by professionals for compliance with the law; identify flows and referrals of the institution to comply with the penal system. Finally, there is an urgent need to create efficient and specific means of attending to pregnant young women, in a comprehensive way, addressing physical, psychological and social aspects, involving and supporting families, in order to mitigate the impacts and the pressures caused by this new situation, guaranteeing the girl the right to have her sexuality guaranteed, quiet and healthy.